Multivariate Regression Analysis of Peer Competition on Emotional Health of High School Students - Lu, Xianghe (International Journal of Social Sciences and Public Administration, 2024)
This study aims to explore the impact of classmate competition on the emotional health of high school students and to examine the mediating role of family support. 450 valid data on this issue from high school students in a certain city were collected, and multivariate regression analysis was used for statistical analysis. The results showed that classmate competition significantly and positively affected students' anxiety levels. The more intense the competition, the stronger the students' anxiety. In addition, family support played a buffering role between classmate competition and emotional health. Higher family support can effectively reduce students' anxiety levels. The study also found that control variables such as gender and grade had a certain impact on emotional health, but it was relatively small. This study emphasizes the importance of improving the educational environment and strengthening family support to promote students' mental health development. In summary, this study provides important empirical evidence for education management and policy making, which will help to better pay attention to and improve students' emotional health issues in practice.